(untitled) - Levinson, Paul (New York, N.Y., 2004)
Levinson (communications and media studies, Fordham U.) entertainingly traces the revolution in mobility in media<--> especially the social impact of cellphones. He includes period illustrations of early telephones, and an annotated bibliography. Although the Internet takes us everywhere in cyberspace, it usually requires us to be seated behind a desk. In contrast, the cellphone lets us walk through the world, fully connected. Cellphone explores the history of mobility in media--from books to cameras to transistor radios to laptops--and examines the unique impact of a device that sits in a pocket or palm, and lets us converse by voice or text. The restricting and liberating edge of accessibility transforms restaurants, public transport, automobiles, romance, literacy, parent-child relationships, war, and indeed all walks of life, trivial and profound. Like an organic cell that moves, evolves, combines with other cells, and generates, the cellphone has become a complex sparkplug of human life.
Keywords: Cellular telephone systems,Cellular telephones; Popular works,Popular works